2014
DOI: 10.1209/0295-5075/106/47005
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model for negative giant magnetoresistance in ultrahigh-mobility 2D electron systems

Abstract: -We report on theoretical studies of the recently discovered negative giant magnetoresistance in ultraclean two-dimensional electron systems at low temperatures. We adapt a transport model to a ultraclean scenario and calculate the elastic scattering rate (electron-charged impurity) in a regime where the Landau level width is much smaller than the cyclotron energy. We obtain that for low magnetic fields the scattering rate and, as a consequence, the longitudinal magnetoresistance dramatically drop because of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…More specifically, in the presence of a parallel component of magnetic field the scattering of the electrons with the lattice increases. Consequently, the scattering rate rises and the huge magnetoresistance vanishes [9]. In contrast the peak around zero magnetic field is left unchanged for all tilt angles as a function of perpendicular magnetic field.…”
Section: Fig 1 (Color Online)mentioning
confidence: 88%
“…More specifically, in the presence of a parallel component of magnetic field the scattering of the electrons with the lattice increases. Consequently, the scattering rate rises and the huge magnetoresistance vanishes [9]. In contrast the peak around zero magnetic field is left unchanged for all tilt angles as a function of perpendicular magnetic field.…”
Section: Fig 1 (Color Online)mentioning
confidence: 88%
“…By now, a number of experimental and theoretical [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] studies have been carried out on the photo-excited transport in low dimensional systems. In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] .…”
mentioning
confidence: 99%
“…In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] . One emerging theory suggests that some of the observed features of the larger negative giant magnetoresistance effect could be a signature of a viscous electron liquid in the low magnetic field quasi ballistic transport regime.…”
mentioning
confidence: 99%
“…As a consequence, the study of potential new mechanisms for realizing GMR in semiconductors has been a useful line of basic research78910. Semiconductor GMR in disordered 2D electronic systems has also been a topic of interest from the fundamental physics perspective111213141516171819202122232425262728, providing insight into weak localization1117, weak anti-localization1117, electron-electron interaction-induced magnetoresistance1114151618192223, metal-insulator transitions induced by a magnetic field29, and GMR in the quantum Hall regime3031.…”
mentioning
confidence: 99%